Improved droop control strategy for distributed photovoltaic power generation systems - Zhengwan, Deng; Ningyu, Gao; Yali, Zhu (Frontiers in Energy Research, 2024)
The control strategy of distributed photovoltaic power generation system (PV) in microgrid consists of inner loop controller and outer loop controller. The inner loop controller is divided into two types, the maximum power point tracking (MPPT) and DC bus voltage support strategy. Switching two control strategies results in a DC bus overvoltage, system oscillation and even PV system down. An improved droop control strategy with a novel inner loop controller is proposed, it applies an output power derivative regulator. Without switching the controller structure, the control system unifies MPPT and DC bus voltage support strategy. A simulation model is built to verify the effectiveness of proposed control strategy, and the results show that the ripple of DC bus voltage decreases more than 60%.